2011
DOI: 10.1016/j.mvr.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background determines mouse strain differences in inflammatory angiogenesis

Abstract: Inflammation and angiogenesis are key components of fibrovascular tissue growth, a biological event underlying both physiological (wound healing) and pathological conditions (tumor development, chronic inflammation). We investigated these components in three frequently used mouse strains (Swiss, Balb/c and C57BL/6J) to verify the influence of genetic background on the kinetics of inflammatory cell recruitment/activation, neovascularization, extracellular matrix deposition, and cytokine production in polyether-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 34 publications
5
49
0
2
Order By: Relevance
“…The subcutaneous sponge model, a well-established model for angiogenesis investigation was chosen due to the possibility to study the role of antigens of T. cruzi instead of live parasites. Studies involving the sponge model showed that this model presents an initial phase (1-3 days) with the predominance of neutrophils, an intermediate stage (4-8 days) with the predominance of macrophages and a final stage (8-15 days) where there is reduction of inflammatory cells with the predominance of blood vessels and collagen in the matrix of the sponge (Andrade et al, 1987;Barcelos et al, 2005;Teixeira et al, 2005;Marques et al, 2011). This is the first study involving administration of total antigen of the Y strain of T. cruzi and as demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcutaneous sponge model, a well-established model for angiogenesis investigation was chosen due to the possibility to study the role of antigens of T. cruzi instead of live parasites. Studies involving the sponge model showed that this model presents an initial phase (1-3 days) with the predominance of neutrophils, an intermediate stage (4-8 days) with the predominance of macrophages and a final stage (8-15 days) where there is reduction of inflammatory cells with the predominance of blood vessels and collagen in the matrix of the sponge (Andrade et al, 1987;Barcelos et al, 2005;Teixeira et al, 2005;Marques et al, 2011). This is the first study involving administration of total antigen of the Y strain of T. cruzi and as demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the infiltration of mononuclear cells into the implants was quantified by measuring the levels of the lysosomal enzyme Nacetyl-β-D-glucosaminidase (NAG) which is present in high levels in activated monocytes/macrophages (Barcelos et al, 2004;Marques et al, 2011). Part of the pellet that remained after the hemoglobin measurement was kept for this assay.…”
Section: Quantification Of Neutrophil Infiltration By Myeloperoxidasementioning
confidence: 99%
“…The extent of the vascularization of the sponge was assessed in terms of the amount of Hb that was detected in the tissue using the aforementioned Drabkin method [27][28][29][30]. The Hb concentration in the samples was determined spectrophotometrically by measuring the absorbance at 540 nm.…”
Section: Determination Of Vegf Levels Hb Content and Mpo And Nag Actmentioning
confidence: 99%
“…The Hb content in the implant was expressed as g Hb per mg wet weight. The cytokine VEGF was measured following the protocol described in previously published studies [28,30]. The neutrophils in the sponge were measured by assaying the MPO activity, as has been described in the literature [27][28][29][30].…”
Section: Determination Of Vegf Levels Hb Content and Mpo And Nag Actmentioning
confidence: 99%
See 1 more Smart Citation